Azirinyl-Substituted Nitrile Oxides: Generation and Use in the Synthesis of Isoxazole Containing Heterocyclic Hybrids - Alexander S. Dudik; Timur O. Zanakhov; Ekaterina E. Galenko; Mikhail S. Novikov; Alexander F. Khlebnikov (Molecules, 2025)
The procedure for the generation of azirinyl-substituted nitrile oxides by the reaction of 2-(diazoacetyl)-2H-azirines with tert-butyl nitrite while preserving the azirine ring has been developed. The [3+2] cycloaddition of azirinyl-substituted nitrile oxides to terminal acetylenes produced azirinyl(isoxazolyl)ketones with various substituents in position 3 of azirine and position 5 of isoxazole fragments in a 51–91% yield at room temperature in DCM. DFT calculations and experimental data are consistent with the assumption that the formation of azirinyl-substituted nitrile oxides is accelerated by the acid catalyst. Cycloadducts of nitrile oxides with aryl/hetarylacetylenes and DMAD can be obtained by catalysis with boron trifluoride etherate, which significantly expands the scope of application of the reaction. Expansion of the azirine ring of the prepared cycloadducts allows obtaining a wide range of structurally diverse functionalized isoxazole-containing heterocyclic hybrids. LED light induces isomerization of the azirinecarbonyl moiety of the azirinyl(isoxazolyl)ketones, resulting in the formation of a set of 3,5’-biisoxazoles in a 40–71% yield, while the catalytic reaction of the azirine moiety with 1,3-diketones opens the way to pyrrole- and isoxazole-containing hybrids. 2-(Isoxazole-3-ylcarbonyl)-3-arylazirines were also easily isomerized to 3-(oxazol-5-yl)isoxazoles in methanol in the presence of excess potassium carbonate at room temperature.